A ESCOLA QUE DE TANTO SER VISTA, NINGUÉM VÊ: a partir das narrativas dos professores de Projeto de Vida - Carolina Moraes Lino (2023)
This research is part of studies on the implementation movement of the Integral Education Program in the state schools of Mato Grosso do Sul in the year 2017, specifically School of Authorship. In this sense, Secondary Education underwent new curricular arrangements, including the Life Project discipline, with the centrality of the pedagogical model between the SED and ICE partnership. In this way, we aim to investigate the different ways of producing schools, through narratives of the Life Project teacher, of High School in Full Time - School of Authorship, in the municipality of Campo Grande, of the State Education Network of the State of Mato Grosso do Sul, starting from the following problem: Is it possible for the Life Project teacher, in an environment of such diverse experiences, to invent/create other schools within the same school? The narratives are produced through oral interviews, understanding Oral History as a research methodology, which represents listening to their history, which is crossed by these practices in their school routine. At first glance, it appears that the School of Authorship is understood as a practice based on alliances between public and private institutions that establish a certain way of occupying the school, from the perspective of neoliberal policies that insist on transforming the school into a company. In the interviews, the teachers, when describing their practices during Life Project classes, explain in the power of differences what makes it possible for us to divert flows, conduct ourselves in a different way, sabotage the gear that tries to hide us, thus overcoming centralizing practices in transmission of knowledge, producing deviations, making it possible to invent/create other schools within the same school. Keywords: Oral History. School of Authorship. Comprehensive Education. Life Project.